2011
DOI: 10.1007/s10457-011-9386-3
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of soil invertebrates in annual crops, agroforestry and forest ecosystems in the Nilgiri biosphere reserve of Western Ghats, India

Abstract: Biologically mediated soil processes rely on soil biota to provide vital ecosystem services in natural and managed ecosystems. However, land use changes continue to impact on assemblages of soil biota and the ecosystem services they provide. The objective of the present study was to assess the effect of land use intensification on the distribution and abundance of soil invertebrate communities in the Nilgiri, a human-dominated biosphere reserve of international importance. Soil invertebrates were sampled in 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Land use intensification can reduce the abundance and diversity of spider species through physical removal, destruction of their microhabitats or through changing the microclimatic conditions within the habitat. Previous studies in the Western Ghats have also indicated the effects of land use changes on the diversity of soil biota (Rossi and Blanchart 2005;Rahman et al 2011;Mandle and Ticktin 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use intensification can reduce the abundance and diversity of spider species through physical removal, destruction of their microhabitats or through changing the microclimatic conditions within the habitat. Previous studies in the Western Ghats have also indicated the effects of land use changes on the diversity of soil biota (Rossi and Blanchart 2005;Rahman et al 2011;Mandle and Ticktin 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Western Ghats mountain ranges of India, by far the most densely populated global biodiversity hotspot (Cinacotta et al 2000), has a mosaic of natural, semi-natural and agro-ecosystems in close proximity to one another. Human-induced changes in land use are globally ubiquitous and specifically of high importance in the Western Ghats (Rahman et al 2011). With an increase in anthropogenically dominated habitats, previously abundant natural habitats have become smaller and more fragmented (Kumara et al 2004;Chakraborty et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are generally used on rubber plantations, for example, to kill weeds, and are a possible factor producing the observed differences in soil metazoan diversity, as they are toxic to non-target species including soil animals 83,84 . A prevalent management practice in rubber plantations is repeated application of glyphosate, (alone or in a mixture with other pesticides) 31 which increases the presence of glyphosate residues in soils 8588 and can be detected in top soils even after two years since the last spraying 86 .…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated soil erosion, along with crop intensification, not only affects soil fertility but also the below-and aboveground biodiversity, including crop genetic diversity and wild diversity which finally reduces the SOM content (Hobbs et al 2008;Pimentel and Burgess 2013). Land use changes cause significant alterations in soil fauna and flora (Rossi and Blanchart 2005;Rahman et al 2012) which are affecting long-term biodiversity in SA.…”
Section: Below-and Above-ground Biodiversity Lossesmentioning
confidence: 99%